How to deal with charge in the ranking of lewis acidity: critical evaluation of an extensive set of cationic lewis acids - Erdmann, Philipp; Schmitt, Manuel; Sigmund, Lukas M.; Krämer, Felix; Breher, Frank; Greb, Lutz (Angewandte Chemie. International edition, 2024)
The quantification of Lewis acidity is of fundamental and applied importance in chemistry. However, if neutral and charged Lewis acids are compared, a coherent ranking has been elusive, and severe uncertainties were accepted. With this study, we present a systematic computational analysis of Lewis base affinities of 784 mono-, di- and tricationic Lewis acids and their comparison with 149 representative neutral Lewis acids. Evaluating vacuum fluoride ion affinities (FIA) reveals a charge-caused clustering that prohibits any meaningful ranking. Instead, solvation-corrected FIAsolv is identified as a metric that overcomes charge sensitivity in a balanced manner, allowing for a coherent evaluation of Lewis acidity across varying charge states. Analyzing the impact of molecular volume on solvation-induced FIA damping provides rationales for fundamental trends and guidelines for the choice or design of neutral and cationic Lewis acids in the condensed phase. Exploring alternative scales, explicit counteranion effects, and selected experimental case studies reaffirms the advantages of solvation-corrected FIAsolv as the most versatile and practical approach for the quantitative ranking of general (thermodynamic) Lewis acidity.